Effect of plasma assisted combustion on emissions of a premixed nitrous oxide fuel blend - Boj N. Villanueva; Po-Hung Lin; Yueh-Heng Li; Jaime P. Honra (Results in Engineering)
Hydrocarbon/Nitrous Oxide fuel blends, commonly called HyNOx or NOFBX, are currently being researched for aeronautic and aerospace propellant applications due to its good performance and economy. However, research on the fuel blend is relatively scant, especially regarding its emission characteristics, as the composition may produce high NOx emissions, which are harmful to both human society and the environment. This study sought to utilize Nanosecond Pulsed Dielectric Barrier Discharge plasma as an emission control mechanism as not only has it found success as a pollution control mechanism, but also as a combustion enhancement one. Chemiluminescence imaging was used to observe the changes in radical species emissions for a laminar premixed CH4/N2O/Ar flame under plasma actuation and emission results were measured with a flue gas analyzer. It was found that once the input voltage crossed a critical value, the chemiluminescent concentrations of CH* and NH2* saw a significant rise, leading non-monotonic increase in the concentration of NOx with this phenomenon lessening as equivalence ratios increased, with the stoichiometric emissions being relatively unaffected. This occurrence was speculated to be from the plasma promotion of the Prompt NO pathway in lean conditions, which was supported by greatly increased OH* radical concentrations. Other emissions such as the Unburned Hydrocarbon CH4 and CO2 were found to decrease non-monotonically with increasing plasma intensity after the input voltage crossed the critical value, with the result being a product of various plasma combustion enhancement mechanisms such as dissociation and excitation.